Nutritional Evaluation of Alkali Treated Neem Kernel Cake Fed to Fattening Uda Rams - Aruwayo, A.; Maigandi, S.A.; Malami, B.S.; Daneji, A.I.; Saulawa, L.A.; Garba, M.G. (Pakistan Journal of Nutrition, 2013)
The study was conducted to evaluate the growth performance and nutrient digestibility of fattening Uda rams fed Alkali treated neem kernel cake. The experiment was conducted at the Teaching and Research Farm of Usmanu Danfodiyo University. Sixteen Uda rams were randomly allotted to treatment diets A, B, C and D with 0, 8.33, 16.67 and 24.99% levels of inclusion of ATNKC, respectively. The study lasted for 105 days consisting of 84 days feeding trial and 21 days of digestibility trial which comprised of 14 days for adaption and seven days for collection of feaces. The dry matter digestibility for all the nutrients in the control and test diets was comparable. The performance of the sheep in treatment B recorded the best ADG of 166.67g/day and highest dry matter intake in treatment A. It was recommended in the study that alkali treated neem kernel cake can be safely included in feed of sheep up to 24.99% for the rams.